EVALUATION OF AGE AND GENDER-RELATED BALANCE SCORES IN NORMAL ADULTS USING MINI BALANCE EVALUATION SYSTEMS TEST (International Journal of Physiotherapy, 2017)
Background: Balance is the ability to maintain body’s center of mass over its base of support. Impairments of balance are common. The purpose of this study was to assess the effect of age and gender on Mini-BES Test balance score among healthy adult subjects.Methods: A cross-sectional study was done, including240 healthy adults. Balance was assessed using Mini-BESTest and data was analyzed for the effect of age and gender on balance scores using two-way ANOVA. The comparison between male and female age groups was analyzed using Unpaired ‘t’ test.Result: The inferential statistics of two-way ANOVA had shown the mean ±SD of balance score was 27.85 ± 0.36, 27.5 ± 0.5,27.5 ± 0.5, 26.45 ± 0.5 for Group1,2,3 and 4 respectively with F = 2.643 (p